Answer:
![t=(p)/((s_1-s_2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/moeh4ftl8rvyafycik2l3tc8cc6jc04fcq.png)
Explanation:
It is given that, p = s Subscript 1 Baseline t minus 2 Subscript 2 Baseline t. It can also written as :
![p=s_1t-s_2t](https://img.qammunity.org/2021/formulas/mathematics/high-school/itw2izmssewya7edbu7u2vw2puz2pr1w6g.png)
We need to solve the above equation for t.
Taking t common on RHS of the equation :
![p=(s_1-s_2)t](https://img.qammunity.org/2021/formulas/mathematics/high-school/ci90858byyzcil0jpkl5fvgikqk95g4dce.png)
Now dividing both sides by
, so,
![(p)/((s_1-s_2))=((s_1-s_2))/((s_1-s_2))t\\\\t=(p)/((s_1-s_2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/pw0xgz03lvr302rvnnhjmjjxc2v3cksh6n.png)
So, the equation for t is :
![t=(p)/((s_1-s_2))](https://img.qammunity.org/2021/formulas/mathematics/high-school/moeh4ftl8rvyafycik2l3tc8cc6jc04fcq.png)